Zasady prawne obrotu celnego towarów po Brexicie między Zjednoczonym Królestwem a UE - Gwardzińska, Ewa; Marak, Katarzyna (PRAWO i WIĘŹ, 2025)
The aim of this paper is to analyse the regulatory scope of the EU-UK Trade and Cooperation Agreement in the aspect of customs turnover of goods, with particular emphasis on its legal principles. The main research problem is to find answers to two research questions: is preferential tariff treatment with a zero duty rate in customs turnover between the UK and the EU the only type of customs turnover and can it be stated that it is duty-free turnover? The analysis shows that duty-free turnover basically concerns the fulfilment of the principles of preferential origin of goods. Failure to fulfil them results in determining the duty due in accordance with the calculation elements. The analysed issues are significant and important from the point of view of customs turnover, but are little recognised in the literature on the subject.